Activation of histamine type 2 receptors enhances intrinsic excitability of medium spiny neurons in the nucleus accumbens. (13th April 2022) - Aceto, Giuseppe; Nardella, Luca; Nanni, Simona; Pecci, Valeria; Bertozzi, Alessia; Colussi, Claudia; D'Ascenzo, Marcello; Grassi, Claudio
Abstract : Abstract: Histaminergic neurons are exclusively located in the hypothalamic tuberomammillary nucleus, from where they project to many brain areas including the nucleus accumbens (NAc), a brain area that integrates diverse monoaminergic inputs to coordinate motivated behaviours. While the NAc expresses various histamine receptor subtypes, the mechanisms by which histamine modulates NAc activity are still poorly understood. Using whole‐cell patch‐clamp recordings, we found that pharmacological activation of histamine 2 (H2) receptors elevates the excitability of NAc medium spiny neurons (MSNs), while activation of H1 receptors failed to significantly affect MSN excitability. The evoked firing of MSNs increased after seconds of local H2 agonist administration and remained elevated for minutes. H2 receptor (H2R) activation accelerated subthreshold depolarization in response to current injection, reduced the latency to fire, diminished action potential afterhyperpolarization and increased the action potential half‐width. The increased excitability was protein kinase A‐dependent and associated with decreased A‐type K + currents. In addition, selective pharmacological inhibition of the Kv4.2 channel, the main molecular determinant of A‐type K + currents in MSNs, mimicked and occluded the increased excitability induced by H2R activation. Our results indicate that histaminergic transmission in the NAc increases MSN intrinsic excitability through H2R‐dependent modulation of Kv4.2 channels. Activation of H2R will significantly alter spike firing in MSNs in vivo, and this effect could be an important mechanism by which these receptors mediate certain aspects of goal‐induced behaviours. Key points: Histamine is synthesized and released by hypothalamic neurons of the tuberomammillary nucleus and serves as a general modulator for whole‐brain activity including the nucleus accumbens. Histamine receptors type 2 (HR2), which are expressed in the nucleus accumbens, couple to Gαs/off proteins which elevate cyclic adenosine monophosphate levels and activate protein kinase A. Whole‐cell patch‐clamp recordings revealed that H2R activation increased the evoked firing in medium spiny neurons of the nucleus accumbens via protein kinase A‐dependent mechanisms. HR2 activation accelerated subthreshold depolarization in response to current injection, reduced the latency to fire, diminished action potential medium after‐hyperpolarization and increased the action potential half‐width. HR2 activation also reduced A‐type potassium current. Selective pharmacological inhibition of the Kv4.2 channel mimicked and occluded the increased excitability induced by H2R activation. Abstract : Abstract figure legend Pharmacological activation of histamine receptor type 2 (H2R) elevates the frequency of evoked firing in medium spiny neurons (MSNs) of the nucleus accumbens (NAc). The mechanism underling this effect requires protein kinase A‐dependent phosphorylation and downregulation of Kv4.2 channels, the molecular determinant of A‐type K + currents.